2014
DOI: 10.1155/2014/212576
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Paracetamol on NOS, COX, and CYP Activity and on Oxidative Stress in Healthy Male Subjects, Rat Hepatocytes, and Recombinant NOS

Abstract: Paracetamol (acetaminophen) is a widely used analgesic drug. It interacts with various enzyme families including cytochrome P450 (CYP), cyclooxygenase (COX), and nitric oxide synthase (NOS), and this interplay may produce reactive oxygen species (ROS). We investigated the effects of paracetamol on prostacyclin, thromboxane, nitric oxide (NO), and oxidative stress in four male subjects who received a single 3 g oral dose of paracetamol. Thromboxane and prostacyclin synthesis was assessed by measuring their majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…In our study, the levels of oxidative stress molecules (NOx and MDA) significantly increased after APAP administration (250 mg/kg) (Table II, Figures 4 and 5). Similar results were reported by other authors, thus, the suggested mechanism is APAP-induced activation of endothelial nitric oxide synthase (eNOS) and inducible nitric oxide synthase (iNOS) in hepatocytes (47). Other authors have reported that APAP can induce liver injury via an oxidative stress mechanism caused by increased MDA production (48).…”
Section: Liposomal Curcumin Effect On Hepatic Function and Oxidative supporting
confidence: 72%
“…In our study, the levels of oxidative stress molecules (NOx and MDA) significantly increased after APAP administration (250 mg/kg) (Table II, Figures 4 and 5). Similar results were reported by other authors, thus, the suggested mechanism is APAP-induced activation of endothelial nitric oxide synthase (eNOS) and inducible nitric oxide synthase (iNOS) in hepatocytes (47). Other authors have reported that APAP can induce liver injury via an oxidative stress mechanism caused by increased MDA production (48).…”
Section: Liposomal Curcumin Effect On Hepatic Function and Oxidative supporting
confidence: 72%
“…Aceta-minophen (1000 µM) was found to inhibit CYP3A4 activity (by 30%), a major CYP isoform contributing to cis-EpOA formation [3]. The temporary almost 6fold increase in cis-EpOA seen in two healthy subjects who ingested 3 g acetaminophen at once could be due to an acetaminophen-induced short-term release of secretory hepatic phospholipase A2 (sPLA2) [7]. This may also have occurred in the acetaminophen-suicided persons of the present study.…”
Section: Discussionmentioning
confidence: 49%
“…The highest serum cis-EpOA concentration of 3723 nM is about 100 times the mean plasma cis-EpOA concentration measured in healthy subjects [3]. Except for two patients, circulating acetaminophen concentrations were higher than the highest acetaminophen plasma concentrations measured in four healthy subjects after ingestion of 3000 mg acetaminophen at once [7].…”
Section: Resultsmentioning
confidence: 70%
“…Intake of a single oral dose of 3 g of paracetamol (acetaminophen) by four healthy male subjects did not result in noteworthy changes in plasmatic urinary concentrations of 15(S)-8-iso-PGF 2␣ , prostaglandin E 2 (PGE 2 ) and the thromboxane (Tx) A 2 (TxA 2 ) metabolite 2,3-dinor-TxB 2 [1], while the urinary excretion of the prostacyclin metabolite 2,3-dinor-6-keto-PGF 1␣ was potently and sustainably inhibited [23]. Interestingly, there was a close correlation between 15(S)-8-iso-PGF 2␣ and 2,3-dinorTxB 2 (Fig.…”
Section: Effect Of High-dosed Paracetamol On 15(s)-8-iso-pgf 2s Ynthementioning
confidence: 97%
“…Selected published findings obtained from the application of these protocols in vitro and in vivo studies are outlined below [17][18][19][20][21][22][23][24][25]. …”
Section: Biomedical Applicationsmentioning
confidence: 99%